A arte do teatro de bonecos como disparadora de encontros na constituição dos curriculosafetos na escola - Pereira, Dulcimar (2013)
The current study intends to present the meetings/gatherings produced between dolls and the school community of EMEF Tancredo de Almeida Neves, located in São Pedro III neighborhood–district of Vitória, in the constitution of their curriculumaffections. In the meetings, some knowledge was produced with constant exchanges among the ones practicing the everyday life. This way, the study main goal is to map the experiences of that group with dolls and stories, as well as the meetings developments. It has as theoretical intercessor: Spinoza (2008) and his contribution related to the good gatherings that increase the power of acting; Foucault (2006) and his studies about the esthetics of existence and people’s care with their own selves and the others; Deleuze (1992) and the intercessors importance; still constitute the intercessor dialogues that discuss about the production of curriculums in the daily school life, as Ferraço (2003), Alves (2004), Carvalho (2009), among others. The methodological paths are constituted during the mapping intercession with studies regarding everyday life. In order to produce data in this space-time, videos, conversations, pictures and pedagogical workshops were used. The study stands out that in those meetings between intercessors-dolls, instructor and student, the power of acting is increased and other proposals are elaborated in the weaving of knowledge and sympathy nets. the work concludes that the good meetings with the dolls theater art composed more colorful mosaics, which enlarged knowledge creating more fluid relations, less tense and that amid the molars and molecular lines were also produced escaping lines that instigated, provoked other movements, enabling the acting power to increase through the exchanges and the production of affection with other meanings of experiencing the school through the ethics-policy based on the each one self-care and the care with others, the existence ethics.